Towards dynamically monitoring computer-assisted instruction to reduce educational inequality. (3rd July 2022) - Chevalère, J.
ABSTRACT: Educational inequality may entail not only socioeconomic disparities, but also cognitive-affective disparities across students. Considering the pervasive socio-contextual factors inherent to classroom environments affecting students' self-confidence and learning – e.g., stereotype threats linked to low cognitive abilities or disadvantaged socioeconomic backgrounds – I envision the possibility to administer and monitor computer-assisted instruction dynamically to fit individual learner needs as a way to minimise, when needed, the influence of contextual factors and enhance self-perceptions to better help students cope with other classmates in group settings. This approach, which represents a neglected possibility so far, may be of interest for researchers and teachers in their daily practice and may stimulate the debate on educational inequality.